Fuzzy Adaptive Control for Direct Torque in Electric Vehicle - Medjdoub khessam; Abdeldejbar Hazzab; Bouchiba Bousmaha; M Bendjima (Institute of Advanced Engineering and Science, 2014)
This paper presents a technique to control the electric vehicle (EV) speed and torque at any curve. Our propulsion model consist of two permanent magnet synchronous (PMSM) motors. The fuzzy adaptive PI controller is used to adjust the different static error constants, as per the speed error. The suggested based on the direct torque fuzzy control (DTFC). A Mamdani type fuzzy direct torque controller is first developed and then rules are modified using stator current membership functions. The computations are ensured by the electronic differential, this driving process permit to steer each driving wheels at any curve separately.Modeling and simulation are carried out using the Matlab/Simulink tool to investigate the performance of the proposed system.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6372